Correlation and Reliability of Behavioral and Otoacoustic-Emission Estimates of Contralateral Medial Olivocochlear Reflex Strength in Humans - Marrufo-Pérez, Miriam I.; Johannesen, Peter T.; Lopez-Poveda, Enrique A. (Frontiers in Neuroscience, 2021)
The roles of the medial olivocochlear reflex (MOCR) in human hearing have been widely investigated but remain controversial. We reason that this may be because the effects of MOCR activation on cochlear mechanical responses can be assessed only indirectly in healthy humans, and the different methods used to assess those effects possibly yield different and/or unreliable estimates. One aim of this study was to investigate the correlation between three methods often employed to assess the strength of MOCR activation by contralateral acoustic stimulation (CAS). We measured tone detection thresholds (N=28), click-evoked otoacoustic emission (CEOAE) input/output (I/O) curves (N=18), and distortion-product otoacoustic emission (DPOAE) I/O curves (N=18) for various test frequencies in the presence and the absence of CAS (broadband noise of 60 dB SPL). As expected, CAS worsened tone detection thresholds, suppressed CEOAEs and DPOAEs, and horizontally shifted CEOAE and DPOAE I/O curves to higher levels. However, the CAS effect on tone detection thresholds was not correlated with the horizontal shift of CEOAE or DPOAE I/O curves, and the CAS-induced CEOAE suppression was not correlated with DPOAE suppression. Only the horizontal shifts of CEOAE and DPOAE I/O functions were correlated with each other at 1.5, 2, and 3 kHz. A second aim was to investigate which of the methods is more reliable. The test-retest variability of the CAS effect was high overall but smallest for tone detection thresholds and CEOAEs, suggesting that their use should be prioritized over the use of DPOAEs. Many factors not related with the MOCR, including the limited parametric space studied, the low resolution of the I/O curves, and the reduced numbers of observations due to data exclusion likely contributed to the weak correlations and the large test-retest variability noted. These findings can help us understand the inconsistencies among past studies and improve our understanding of the functional significance of the MOCR.